The electrodeposition of zinc-manganese - Ferguson, Karen Elizabeth (1999)
Electroplated zinc alloys can provide increased corrosion protection for automotive body panels compared with zinc coatings of similar thickness. As a result, their use is becoming widespread. In particular, outstanding results have been reported in the literature for the corrosion resistance of zinc-manganese, and the alloys are said to offer good paintability, weldability and formability. However, the production of zinc-manganese coatings is restricted by the instability of the sulphate-citrate bath from which the alloy is usually deposited. The solution deteriorates rapidly and precipitates appear in the bath. The aim of this research was to investigate both the process of alloy deposition from the sulphate-citrate bath and the solution instability.